Bioactive poly(ε-caprolactone) microspheres with tunable open pores as microcarriers for tissue regeneration. (April 2019) - Zhou, Anmin; Ye, Zhaoyang; Zhou, Yan; Tan, Wen-song
Microparticles with porous structure can be applied as microcarriers for both cell culture and tissue regeneration. While well-controlled pore structure represents a critical challenge to be achieved. In the present study, in order to develop microcarriers for cell culture, a series of poly(ε-caprolactone) microspheres were fabricated with varied macroporous structures. Poly(ε-caprolactone) microspheres were prepared via the integration of the emulsion/solvent evaporation and particle leaching mechanisms. Particularly, by adjusting poly(ε-caprolactone) concentration and the ratio between the porogen paraffin and poly(ε-caprolactone), the microspheres with the pore size of 25.6–84.0 μm and the porosity of 57.4–75.5% were obtained. Further, the microspheres were subjected to alkaline hydrolysis, followed by surface coating with hydroxyapatite. These porous poly(ε-caprolactone) microspheres with surface modification well supported the adhesion and growth of human fibroblasts. Together, bioactive poly(ε-caprolactone) microspheres with controlled pore structure are potential to be applied in cell culture and tissue regeneration.